Humidity, temperature and air velocity data logger for thermal comfort application - Rashila Baharudin (Universiti Malaysia Perlis, 2008)
The mistreat operation of an air conditioning system will affect human welfare and health such as headaches and drowsiness. Because of this problem a thermal comfort application must be created to overcome this problem. This project is to create a thermal comfort system in different environment such as seated relaxed, clock repairer, laboratory and others. It measures the temperature and humidity using respective sensor that connected to a Data Logger and Lab VIEW. From this temperature and humidity value, the thermal comfort can be found by observing the value of PMV. The selection of environment or metabolic heat and clothing insulation for this project are fixed to some value that are almost the same and have not much different to ease the calculation. They are fixing to some variable that have the same application. By selecting the suitable metabolic heat and clothing insulation, thermal comfort can be achieved. After observing the graph of PMV versus temperature and humidity, the value of thermal comfort can be found and we need to adjust the setting of air conditioning manually after the system measure the different between the comfort temperature and temperature of the air conditioning. From this system, thermal comfort can be developed to recognize temperature and humidity to produce a thermally comfortable environment for different situation.